Analisis Tata Kelola Keamanan Indonesia Masa Kini: Studi Kasus UU No. 34/2004, UU No. 2/2002, UU No. 7/20121 - Maksum, Ali; Surwandono, Surwandono (Jurnal Keamanan Nasional, 2020)
This article discusses the analysis of security governance about three important laws, namely (1) Law no. 34/2004 on the Indonesian National Army (TNI), (2) Law no. 2/2002 on the Indonesian National Police (POLRI), and (3) Law. No. 7/2012 on Social Conflict Management. This discussion is imperative to understand the main duties, roles, and functions of the TNI / POLRI as the front guard in maintaining national security. This article argues that there is a positive relationship between the ineffectiveness of regulations on Indonesia’s national security and the approach that Indonesia has chosen in managing national security. In addition, the type of approach chosen in defining security issues will be directly proportional to the adopted security policy. Therefore, the discussion of this paper is divided into three sections, namely the analysis of Law no. 34/2004 on TNI, analysis of Law no. 2/2002 on POLRI, Law no. 7/2012 on handling social conflict, and conclusions.